The kinetics and QSAR of abiotic reduction of mononitro aromatic compounds catalyzed by activated carbon. (January 2015) - Gong, Wenwen; Liu, Xinhui; Gao, Ding; Yu, Yanjun; Fu, Wenjun; Cheng, Dengmiao; Cui, Baoshan; Bai, Junhong
Highlights: The kinetics of abiotic reduction of mono-NACs catalyzed by AC in an anaerobic system were examined. The reduction rates varied widely due to the substituents and their positions on the benzene rings. A QSAR model for the reduction rates was developed using 15 quantum chemical descriptors. Abstract: The kinetics of abiotic reduction of mono-nitro aromatic compounds (mono-NACs) catalyzed by activated carbon (AC) in an anaerobic system were examined. There were 6 types of substituent groups on nitrobenzene, including methyl, chlorine, amino, carboxyl, hydroxyl and cyanogen groups, at the ortho, meta or para positions. Our results showed that reduction followed pseudo-first order reaction kinetics, and that the rate constant (log k SA ) varied widely, ranging between −4.77 and −2.82, depending upon the type and position of the substituent. A quantitative structure–activity relationship (QSAR) model using 15 theoretical molecular descriptors and partial-least-squares (PLS) regression was developed for the reduction rates of mono-NACs catalyzed by AC. The cross-validated regression coefficient ( Q cum 2, 0.861) and correlation coefficient ( R 2, 0.898) indicated significantly high robustness of the model. The VIP (variable importance in the projection) values of energy of the lowest unoccupied molecular orbital ( E LUMO ) and the maximum net atomic charge on the aromatic carbon bound to the nitro group ( Q C - ) were 1.15 and 1.01, respectively. These values indicated that the molecular orbital energies and the atomic net charges might play important roles in the reduction of mono-NACs catalyzed by AC in anaerobic systems.